The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/pan.13158
|View full text |Cite
|
Sign up to set email alerts
|

Current use of factor concentrates in pediatric cardiac anesthesia

Abstract: Excessive bleeding following pediatric cardiopulmonary bypass is associated with increased morbidity and mortality, both from the effects of hemorrhage and the therapies employed to achieve hemostasis. Neonates and infants are especially at risk because their coagulation systems are immature, surgeries are often complex, and cardiopulmonary bypass technologies are inappropriately matched to patient size and physiology. Consequently, these young children receive substantial amounts of adult-derived blood produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 64 publications
0
37
0
2
Order By: Relevance
“…[13][14][15][16][17][18][19] Although these advantages of 4F-PCC over FFP may be pertinent for pediatric patients, the optimal indications, dosing, frequency, and adverse effects in children are unknown due to limited experience. [20][21][22][23] Noga et al reported a retrospective experience in a cohort of 16 pediatric patients who received 4F-PCC to treat coagulation disturbances related to cardiac surgery and CPB or due to the administration of vitamin K antagonists. 22 Compared with this study, our patient population was unique because the main indication for 4F-PCC administration was perioperative coagulopathy, primarily secondary to trauma, and medical disorders rather than coagulopathy following CPB or from the administration of vitamin K antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Although these advantages of 4F-PCC over FFP may be pertinent for pediatric patients, the optimal indications, dosing, frequency, and adverse effects in children are unknown due to limited experience. [20][21][22][23] Noga et al reported a retrospective experience in a cohort of 16 pediatric patients who received 4F-PCC to treat coagulation disturbances related to cardiac surgery and CPB or due to the administration of vitamin K antagonists. 22 Compared with this study, our patient population was unique because the main indication for 4F-PCC administration was perioperative coagulopathy, primarily secondary to trauma, and medical disorders rather than coagulopathy following CPB or from the administration of vitamin K antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…8,81 The effects of intraoperative fibrinogen substitution have been investigated in adult studies across a range of clinical settings, but data from pediatric surgical patients are scarce. 79,80,[82][83][84] In a randomized clinical trial performed in children undergoing major craniofacial or spinal surgery, intraoperative fibrinogen concentrate was administered using one of two FIBTEM MCF threshold values as a trigger, < 8 mm (conventional) or < 13 mm (early substitution), to maintain fibrinogen levels throughout surgery. 80 Early substitution led to a significant reduction in blood loss and transfusion of RBCs among children undergoing craniosynostosis surgery, although no significant differences were observed in those undergoing scoliosis surgery (►Fig.…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…84 Three comprehensive reviews of bleeding management during pediatric major surgery have been published in recent years. 83,87,88 All of them emphasized the benefits of goal-directed use of coagulation factors such as fibrinogen concentrate, especially when guided by viscoelastic assays. A meta-analysis of 14 randomized clinical trials involving 1,035 adult and pediatric surgical patients demonstrated that fibrinogen concentrate therapy was associated with reduced bleeding and that it might reduce all-cause mortality.…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…Surgical correction or palliation of complex congenital heart defects in newborns and small infants is often accompanied by severe perioperative bleeding, and almost invariably requires the use of blood components (fresh frozen plasma and platelets) and often of other procoagulant interventions, including fibrinogen concentrate, prothrombin complex concentrate, factor XIII, and even recombinant activated FVII .…”
mentioning
confidence: 99%